Family size and subjective well-being in Europe: Do more children make us (un)happy? - Barbara Pertold-Gebicka; Dominika Spolcova (Charles University in Prague, Institute of Economic Studies (IES), 2019)
With the goal to shed more light on fertility drivers in Europe, we estimate the causal relationship between the number of children and parental subjective well-being using two alternative measures: life satisfaction and a happiness index. Multiple births are used as the source of exogenous variation to deal with number of children endogeneity. Estimating this relationship on subgroups of mothers and fathers whose children fall into different age categories, we document that fathers' well-being is negatively hit by the unexpected increase in family size due to twin birth all across Europe. This effect turns positive as children get older in all European regions when happiness index is investigated and in all regions except for the post-communist countries when life satisfaction is investigated. For mothers we identify larger variation across Europe and over child ages. We show that fathers' reaction to children is mainly driven by their (dis)satisfaction with time allocation and accommodation, while mothers' reaction to additional children at highest child ages is mainly driven by dissatisfaction with job. Region-specific fertility rates are correlated with fathers' marginal utility of additional child.
Keywords: C21; J13; I31; 330; Fertility; subjective well-being